2021
DOI: 10.24191/jmeche.v18i1.15181
|View full text |Cite
|
Sign up to set email alerts
|

Free Vibration Analysis of Laminated CNTRC Plates using the pb2-Ritz Method

Abstract: This paper presents the free vibration analysis of laminated functionally graded carbon nanotube reinforced composite (FG-CNTRC) plates. The CNTRC layer consists of single-walled carbon nanotubes (SWCNTs) as reinforcement and polymer as a matrix. The material properties are determined according to the extended rule of mixture. Four different patterns of SWCNTs distribution across the thickness of individual layers are considered. Based on the first-order shear deformation theory (FSDT), the equations of motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The material properties of the FFRE composite plate were obtained from work done by Daoud et al [9], as shown in Table 1, while the dimension of the square plate was set to be 0.25 m. The boundary conditions that will be considered are four-edge simply supported (SSSS), four-edge clamped (CCCC) and cantilever (CFFF). The stacking sequences that were studied in this project are 8 , and [90°] 8 . The delamination sizes considered are 0.0% (intact), 12.5%, 25%, 50%, and 75% square delamination located at the centre and between the middle plies.…”
Section: Delamination Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The material properties of the FFRE composite plate were obtained from work done by Daoud et al [9], as shown in Table 1, while the dimension of the square plate was set to be 0.25 m. The boundary conditions that will be considered are four-edge simply supported (SSSS), four-edge clamped (CCCC) and cantilever (CFFF). The stacking sequences that were studied in this project are 8 , and [90°] 8 . The delamination sizes considered are 0.0% (intact), 12.5%, 25%, 50%, and 75% square delamination located at the centre and between the middle plies.…”
Section: Delamination Sizementioning
confidence: 99%
“…Meon et al [7] developed a three-dimensional progressive damage finite element model to detect delamination and examine the failure modes and structural response of carbon fibre reinforced epoxy composite subjected to low-velocity impact loading. Hung et al [8] conducted a free vibration analysis of laminated functionally graded carbon nanotubereinforced composite (FG-CNTRC) plates with four different patterns of single-walled carbon nanotubes (SWCNTs) by using the pb2-Ritz method.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that GPLs with a bigger surface area and comprising fewer single-GPL laminates may provide better reinforcing influence; however, for GPL aspect ratios and widthto-thickness ratios more than 4 and 1000, critical buckling force and post-buckling path will be almost identical. Furthermore, many studies have been implemented to show that functionally graded nanofiller distribution patterns also play a key role in the structural response of composite structures (Pradhan and Phadikar, 2010;Lei et al, 2015;Zhang et al, 2015;Bui et al, 2016;Lin et al, 2017;Ansari et al, 2018;García-Macías et al, 2018;Lin et al, 2018;Muni Rami Reddy et al, 2018;Shahrjerdi and Yavari, 2018;Yang et al, 2018;Nguyen et al, 2019;Thai et al, 2019;Hung et al, 2021;Saiah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%